A study on natural phytochemicals and antiviral drugs to combat the deadly covid-19- an in silico approach - M., Keerthana; P., Chitra (International Journal of Scientific Research in Biological Sciences, 2020)
Novel coronavirus (COVID-19) cases were first reported in Wuhan, Hubei province of China and have since spread all over the world. The virus is spreading rapidly by human to human transmission despite serious precautions, threatening a pandemic that will affect billions of people. Currently there are no vaccines, monoclonal antibodies or drugs available for SARS-CoV-2. There is an urgent need to identify antiviral compounds that can combat the effects of this deadly virus. In this review, an effort is taken to perform molecular docking of some natural phytochemicals to 2019-nCoV spike receptor-binding domain. The docking studies were carried out in Autodock 4.2.6 and the drug likeness properties were predicted using SwissADME webserver. The results revealed that quercetin (-8.71 Kcal/mol) and theaflavin (-7.36 Kcal/mol) from Camellia sinensis had best binding scores with 2019-nCoV spike receptor-binding domain.